Surgeon specific mortality in adult cardiac surgery: comparison between crude and risk stratified data. Issue 7405 (3rd July 2003) - Bridgewater, Ben; Grayson, Anthony D; Jackson, Mark; Brooks, Nicholas; Grotte, Geir J; Keenan, Daniel J M; Millner, Russell; Fabri, Brian M; Mark, Jones
Abstract: Objective As a result of recent failures in clinical governance the government has made a commitment to bring individual surgeons' mortality data into the public domain. We have analysed a database to compare crude mortality after coronary artery bypass surgery with outcomes that were stratified by risk. Design Retrospective analysis of prospectively collected data. Setting All NHS centres in the geographical north west of England that undertake cardiac surgery in adults. Participants All patients undergoing isolated bypass graft surgery for the first time between April 1999 and March 2002. Main outcome measures Surgeon specific postoperative mortality and predicted mortality by EuroSCORE. Results 8572 patients were operated on by 23 surgeons. Overall mortality was 1.7%. Observed mortality between surgeons ranged from 0% to 3.7%; predicted mortality ranged from 2% to 3.7%. Eighty five per cent (7286) of the patients had a EuroSCORE of 5 or less; 49% of the deaths were in this lower risk group. A large proportion of the variability in predicted mortality between surgeons was due to a small but differing number of high risk patients. Conclusions It is possible to collect risk stratified data on all patients undergoing coronary bypass surgery. For most the predicted mortality is low. The small proportion of high risk patients is responsible for most of the differences in predicted mortality between surgeons. Crude comparisons of death rates can be misleading and may encourage surgeons to practise risk averse behaviour. We recommend a comparison of death rates that is stratified by risk and based on low risk cases as the national benchmark for assessing consultant specific performance.